TOURISM IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2021)
A tourist who is at least a little familiar with the history of mankind does not need to ask questions: what is so attractive about tourism in Uzbekistan and what makes it stand out among hundreds of other tourist destinations. Because the answer is obvious. In the same way that this land, called by the ancient Greeks Transoxiana, attracted Alexander the Great almost two and a half millennia ago. What fascinated the Arabs with the land they called Maverannahr - the land of two great Central Asian rivers - the Amu Darya and the Syr Darya, mighty oasis cities inhabited by skilled artisans, the land of generous fields and gardens, giving sun-drenched harvests. The article describes the main sites of tourism in Uzbeksitan.